Effects of early defoliation on the skin phenolic composition of 'Tempranillo' grapevines - Valdés, M. E.; Moreno, Daniel; Gamero, Esther; Talaverano, M. I.; Pérez, Diego; Castel, Juan R.; Intrigliolo, Diego S. (ISHS, 2020)
Early defoliation can be a useful tool to reduce vine yield and improve fruit composition. Previous studies have explored the effects of this technique on the yield components but less effort has been done in order to characterize its impact on the skins phenolic concentration and profile. This work describes the effects of early defoliation on the composition and concentration of phenolic compounds in the grape-skins of 'Tempranillo' grapevines growing in Requena (Valencia, Spain), conducted in a vertical shoot positioning system and irrigated at 75% of crop evapotranspiration during the 2009 season. Control (non-defoliated vines) were compared with defoliation performed either just before anthesis (phenological stage H, treatment ED), or at fruit set (phenological stage J, treatment LD). In both defoliation treatments, all leaves from the first 6 nodes, including laterals leaves, were removed. In a fourth treatment, only the leaves facing east from the first 8 nodes were removed at phenological stage H (treatment EED). A total of 42 phenolic compounds were identified and quantified in the grape skins including anthocyanins, flavonols, and hydroxycinnamic acids, both as simple and as conjugated molecules, and also flavanols (cathechin and epi-cathechin and the flavanol dimmers B1, B2 and B3). The LD treatment significantly increased the concentration of anthocyanidins, such as 3-O-monoglucosides forms and 3-O-acylated monoglucosides from acetic and coumaric acids. Similarly, early defoliation both before anthesis (ED) and at fruit set (LD) significantly increased the concentration of flavonols (glycosides of mirycetin, quercetin, kaempferol and isorhamnetin) as well as flavanols and hydroxycinnamic acids and stilbenes. However, defoliation with less intensity (EED, only the leaves facing east removed), did not significantly alter the grape phenolic profile respect to the Control, non-defoliated vines. Therefore LD treatment may contribute to improve the wine color stability as the concentration of compounds with ability to complex anthocyanins was increased. The potential implications of these effects on wine quality are discussed.